The immunology of experimental Chagas' disease III. rejection of allogeneic heart cells in vitro - Santos-Buch, Charles A. (1974)
Experiments that consisted of incubation of Trypanosoma cruzi-sensitized lymphocytes derived from chronically infected rabbits and from rabbits repeatedly immunized with a small particle or membrane fraction derived from homogenates of T. cruzi forms, showed destruction of allogeneic, parasitized and nonparasitized heart cells in vitro. Mononuclear cells collected from peripheral blood were incubated for 1 h at 37°C to isolate the lymphocytes. Following incubation, over 99% of the cells in the supernate were lymphocytes, which were utilized in these experiments. At the start of these experiments, 70–80% of the sensitized lymphocytes were unattached, small and round, with sparse filipodia. In the ensuing hours, marked heart cell destruction, similar to that seen in an active lesion when lymphocytes invade heart tissue, were observed. After 18 h incubation, about 65–70% of the lymphocytes were attached, larger, and rough surfaced. Inhibition of monocyte migration tests, each in the presence of the antigens of subcellular fractions of T. cruzi organisms and of allogeneic heart myofibers, indicated the presence of a cross-reacting antigen common to both the parasite and the heart in the small particle or membrane fractions. The particulate antigens of the 30,000 g, 35-min fraction of heart muscle gave rise to inhibition of monocyte migration as did the counterpart fraction derived from T. cruzi organisms. The destruction of nonparasitized target heart cells by T. cruzi-sensitized lymphocytes is an in vitro model of the chronic myocarditis of Chagas' disease, and the recognition of cross-reactive antigens of the host cell by T. cruzi-sensitized lymphocytes is believed to be the pathogenic basis for subsequent tissue injury in the chronic phase of this disease.